Conversation time and mental health during the COVID‐19 pandemic: A web‐based cross‐sectional survey of Japanese employees. Issue 1 (10th May 2022) - Izawa, Shuhei; Nakamura‐Taira, Nanako; Yoshikawa, Toru; Akamatsu, Rie; Ikeda, Hiroki; Kubo, Tomohide
Abstract: Objective: During the Coronavirus disease 2019 (COVID‐19) pandemic, social isolation and impaired social interaction could be the factors that cause mental health problems. This study investigated the association between conversation time in daily life and mental health among Japanese employees. Methods: In August 2021, a web‐based cross‐sectional survey was conducted with 1000 Japanese employees. Weekly conversation time was assessed in four domains (family members, friends, someone in the workplace, and others), and mental health was assessed using the Japanese version of the Kessler Psychological Distress Scale (K6 scale). Weekly total conversation time was calculated, and participants were assigned to one of the four conversation time categories based on quantile values to investigate the associations with poor mental health (K6 ≥ 13). Results: The logistic regression analyses revealed that participants with short conversation times (<3.5 h per week) had poorer mental health compared to those with long conversation times (> 21.0 h per week), even after adjusting for confounders (OR = 2.48 [95% CI 1.31–4.71]). For the exploratory analyses of conversation time for each domain, the associations of short conversation time in the workplace with poor mental health was most robust (OR =2.02 [95% CI 1.13–3.63]). Conclusions: Japanese employees with conversation time of <3.5 h per week (i.e., 30 min per day) had poor mental health. During the COVID‐19 pandemic, people have largely limited opportunities to have conversations with others, but a certain level of conversation time might be required to maintain mental health.